2001
DOI: 10.1002/ajmg.10068
|View full text |Cite
|
Sign up to set email alerts
|

A patient defines the interstitial 1q deletion syndrome characterized by antithrombin III deficiency

Abstract: A patient with microbrachycephaly, high forehead, long philtrum, thin upper lip, downturned corners of the mouth, low set ears with overlapping helix, fifth-finger clinodactyly, small hands and feet, bilateral transverse palmar crease, low total finger ridge count, hypotonia, severe growth and psychomotor delay, mild hypoplasia of corpus callosum, and Arnold-Chiari type 1 malformation is reported. The karyotype showed 46, XY, del(1)(q23q31.2). Coagulation factor V (F5, 1q23) and coagulation factor XIII (F13B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Earlier reports indicated that proximal 1q (1q21-q25) deletions present with developmental delay, microcephaly, cardiac, renal and genital abnormalities, and some dysmorphic features (4,5). A submicroscopic deletion with a location similar/identical to the one in the current patients was previously reported by Reddy et al (3).…”
Section: Discussionsupporting
confidence: 70%
“…Earlier reports indicated that proximal 1q (1q21-q25) deletions present with developmental delay, microcephaly, cardiac, renal and genital abnormalities, and some dysmorphic features (4,5). A submicroscopic deletion with a location similar/identical to the one in the current patients was previously reported by Reddy et al (3).…”
Section: Discussionsupporting
confidence: 70%
“…They have been conventionally classified into 3 groups: 1q21-q25, 1q25-q32, and 1q42-qter [Schinzel and Schmid, 1980;Taysi et al, 1982]. Pallotta et al [2001] described a patient with a deletion encompassing 1q23-q31.2, overlapping the proximal and intermediate segment. After reviewing the literature concerning proximal and intermediate 1q deletion syndrome, they hypothesized that there was only one 1q interstitial deletion syndrome clinically characterized by ATIII defi ciency.…”
mentioning
confidence: 99%
“…Structural modeling of the consequences of the S234W point mutation, predicted to alter the hydrophobicity of the protein, was not performed. Although the comparative polar residue in coagulation FVIII (T281 in NP_000123) has been the site of a recurrent described mutation associated with mild hemophilia A (Haemophilia A database, http://europium.csc.mrc.ac.uk/ WebPages/PublicFiles/PointMutationsA.htm, site accessed 29 September 2006), it is possible that the S234W point mutation results in only a neutral amino acid substitution.Syndromes involving an interstitial deletion of 1q have been described in association with AT3 deficiency (encoded by SERPINC1 at 1q23-q25.1) [7], which was not present in this patient. These findings suggest that chromosomal deletion syndromes may be a cause of coagulation factor deficiency, and that assays for occult chromosomal rearrangements could be considered when sequence analysis of a gene coding region does not reveal an expected mutation pattern.…”
mentioning
confidence: 55%
“…Syndromes involving an interstitial deletion of 1q have been described in association with AT3 deficiency (encoded by SERPINC1 at 1q23-q25.1) [7], which was not present in this patient. These findings suggest that chromosomal deletion syndromes may be a cause of coagulation factor deficiency, and that assays for occult chromosomal rearrangements could be considered when sequence analysis of a gene coding region does not reveal an expected mutation pattern.…”
mentioning
confidence: 55%
See 1 more Smart Citation